Legal Review of Child Grooming as A Crime of Sexual Violence in Indonesia - Luh Putu Vera Astri Pujayanti; Sopian; Herlina Sulaiman; Sahrul; Misno (Jurnal Hukum dan HAM Wara Sains, 2023)
The phenomenon of sexual violence is an issue that is increasingly being discussed in Indonesia. Sexual violence can happen to anyone, both women and men, but most victims are women. Children are a group that is very vulnerable to sexual violence because children are always positioned as weak or powerless and have a high dependence on the adults around them. This is what makes children helpless when threatened not to tell what happened. In almost every case uncovered, the perpetrators are people close to the victims. One of the sexual violence that occurs in children is the rise of the child grooming phenomenon in Indonesia, a new form of crime. Child grooming in Indonesia, or sexual exploitation crimes against children using social media, is increasing because the demand for the global sex market is getting bigger. This research uses normative research, which is analytical descriptive through a Statute Approach, techniques through data source studies/data collection carried out by literature (secondary data). The results of this study indicate that child grooming is a practice carried out by adults to attract attention and manipulate minors for sexual purposes or other crimes. In Indonesia, grooming children has been made a crime of violence against children based on Law Number 35 of 2014 concerning Child Protection.